Factors Affecting The Recurrence Of Rheumatic Diseases In The Working Area Of The East Ring Health Center In Bengkulu City In 2024 - Sanjaya, Adi Akbar; Murwati, Murwati; Murya, Kartika (Universitas Dehasen Bengkulu, 2024)
World Health Organization (WHO) in 2016 as many as 335 million people in the world who suffer from rheumatism (Rasiman, N.B & Reskiani,2022).The prevalence of rheumatism in Indonesia is quite high, which is one of 12 non-communicable diseases of rheumatic patients in Indonesia reached 7.30%.The number of rheumatism in Bengkulu province ranked second after Aceh province, amounting to 12.11%.(Ministry of Health, 2018).The purpose of this study was to know the relationship of knowledge with the recurrence of rheumatic diseases, to know the relationship of activity with the recurrence of rheumatic diseases, knowledge of the relationship of diet with the recurrence of rheumatic diseases.Sampling method is done by purposive sampling technique where the researcher takes the sample in accordance with certain considerations. the sample in this study was 75 respondents who were diagnosed with rheumatic disease at the East ring Health Center in bengkulu city in 2024 .From the results of Chi-Square test analysis showed that the value (p=0.001) there is a meaningful relationship between knowledge with rheumatic recurrence, from the results of Chi-Square test analysis showed that the value (p=0.021 )there is a meaningful relationship between activity patterns with rheumatic recurrence, the results of Chi-Square test analysis (continuity correction) showed that the value (p=0.001) puskesmas lingkar timur bengkulu city in 2024.It is hoped that these results to the East Lingkar Health Center can provide useful information and input in preventing and treating this rheumatic recurrence.